Light-Induced Retinopathy: Young Age Protects more than Ocular Pigmentation. (3rd June 2017) - Polosa, Anna; Bessaklia, Hyba; Lachapelle, Pierre
ABSTRACT: Purpose : The purpose of this study was to compare the efficacy that ocular melanin confers in protecting the retina of juvenile and adult rats exposed to a bright luminous environment. Methods : Juvenile (JLE) and adult (ALE) Long–Evans pigmented rats were thus exposed to a bright cyclic light (10, 000lux; white light) from postnatal day 14–28 or for 6 consecutive days, respectively. Flash electroretinograms (ERG) and retinal histology were performed at different predetermined ages, post-light exposure. Results : Despite a significant reduction in ERG responses immediately following light exposure, with time, retinal function fully recovered in JLE compared to a 54% recovery for the ALE. In ALE, we noted a region of the supero-temporal quadrant that was highly vulnerable to light damage. This region was also devoid of melanin granules prior to the light exposure. This melanin-free zone increased in size in the days that followed the end of exposure, a process that was accompanied by the gradual degeneration of the thus uncovered photoreceptors. In contrast, melanin and photoreceptor losses were minimal in JLE. Conclusion : Our results suggest that the light-induced photoreceptor degeneration in ALE would be secondary to the initial destruction of the RPE and ensuing loss of melanin protection. In contrast, the melanin granules of JLE appear to be significantly more resistant to light damage, a characteristic that would explain the higher resistance of JLE photoreceptors to light damage. Our results would thus suggest that the efficacy of ocular melanin protection against light damage declines with age.